2002
DOI: 10.1046/j.1460-9568.2002.02166.x
|View full text |Cite
|
Sign up to set email alerts
|

Ephrin‐B3–EphA4 interactions regulate the growth of specific thalamocortical axon populations in vitro

Abstract: The role was studied of ephrin-B3, a ligand of the Eph family of tyrosine kinase receptors, in the formation of cortical connectivity. In situ hybridization and immunohistochemistry showed that EphA4, a receptor of ephrin-B3, was expressed in the lateral thalamus (visual and somaotosensory thalamus) of the developing rat brain, but not in the medial thalamic nuclei which project to the limbic cortex. Correspondingly, ephrin-B3 was expressed strongly in the developing limbic cortex including amygdala, entorhina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 39 publications
2
34
0
Order By: Relevance
“…Ephrin-B3 has been noted for its remarkably restricted expression pattern down the midline of the neural tube during development (8,38), suggesting that ephrin-B3 may regulate the midline guidance of axons in forming the spinal cord. In addition, it has also been reported that ephrin-B3 guides regional innervation by suppressing axonal growth of lateral thalamic neurons in developing rat brains (39). Thus, ephrin-B3 is likely to play a critical role in the process of neurodevelopment.…”
Section: Discussionmentioning
confidence: 95%
“…Ephrin-B3 has been noted for its remarkably restricted expression pattern down the midline of the neural tube during development (8,38), suggesting that ephrin-B3 may regulate the midline guidance of axons in forming the spinal cord. In addition, it has also been reported that ephrin-B3 guides regional innervation by suppressing axonal growth of lateral thalamic neurons in developing rat brains (39). Thus, ephrin-B3 is likely to play a critical role in the process of neurodevelopment.…”
Section: Discussionmentioning
confidence: 95%
“…distributed (Suzuki et al, 1997;Inoue et al, 1998;Mackarehtschian et al, 1999;Miyashita-Lin et al, 1999;Nakagawa et al, 1999;Yun et al, 2003) and associated with thalamocortical axon growth and guidance (Gao et al, 1998;Takemoto et al, 2002). Ephrin-A5 is one example of a likely mediator of FGF8/17 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In situ hybridization was performed as described (Takemoto et al, 2002;Okabe et al, 2004a) with some modifications. In brief, mRNA probes were labeled with digoxigenin-UTP by RNA in vitro transcription according to the manufacturer's protocol (Roche Diagnostics).…”
Section: In Situ Hybridizationmentioning
confidence: 99%